Is welfare dependency inherited? Estimating the causal welfare transmission effects using Swedish sibling data - Karin Edmark; Kajsa Hanspers (Institute for Labour Market Policy Evaluation (IFAU), 2011)
This study tests whether individuals who grow up with parents on welfare benefits are themselves more (or less) likely to be welfare recipients as young adults, compared to individuals who grow up in non-welfare households. We use the sibling difference method to identify causal effects separately from the effects of correlated factors. While a descriptive analysis reveals a fairly high positive intergenerational correlation, especially in the late teens and conditional on a large set of household level factors, the sibling analysis provides no support for a causal effect of parents' welfare benefit receipt on children's future welfare use.
Keywords: I39; J19; 330; Welfare benefits; intergenerational mobility; sibling approach; Sozialhilfeempfänger; Generationengerechtigkeit; Familie; Schätzung; Schweden